Contractor Drilling with Pounder II - Danert, Kerstin; Carter, Richard C. (Cranfield University, 2001)
This report contributes to the findings, implications, and future plans of a project, initiated by Cranfield University (Silsoe, UK) entitled “Private Sector Participation in Low Cost Water Well Drilling”.
Project Manager Dr Richard Carter, Institute of Water and Environment, Cranfield University at Silsoe.